Improving the Performance of Librarians and Teachers in Managing Libraries as Learning Resources Through Structured Guidance at SD Negeri Sulur Kapanewon Samigaluh Academic Year 2021/2022 - Sumiyarti Sumiyarti (International Journal of Chemistry Education Research, 2022)
This study aims to determine the implementation of a structured coaching program by describing the process of improving the performance of librarians in each cycle (I and II), and knowing the results of improving the performance of librarians and teachers in managing libraries as learning resources through structured coaching at SD Negeri Sulur Kapanewon Samigaluh in the 2021/2022 academic year. used is School Action Research. The research was carried out in two cycles, each cycle consisting of planning, implementing actions, observing, and reflecting. The subject of this research was carried out on all librarians and teachers of SD Negeri Sulur for the academic year 2021/2022. The data collection used in this study is qualitative data with percentages. Qualitative data were obtained from observation sheets on the implementation of structured coaching activities carried out by school principals on librarians and teachers supported by the results of interviews. The results obtained from this study are 1) The process of implementing structured coaching carried out by the principal has increased quite significantly from the first cycle related to the management of final results at the 3rd meeting the average score reached 81.87%; following Cycle II, the 3rd meeting, the average score based on percent reached 92.15%, an increase of 10.28%; The process of implementing structured coaching activities; what the researcher did for 30” (thirty minutes) in the study was said to be successful with the success indicator already exceeding 75%; Cycle II, 3rd meeting; 91.46% increase 18.63%; The results of improved performance in providing services to users have reached more than 75%; The activity of the first cycle of the 3rd meeting; 74.68% while Cycle II is the 3rd meeting; reached 91.36% increase reached 16.68%; The following is the active process of participants in participating in structured coaching. researchers for 30” (thirty minutes) participants in the study were declared successful with indicators of success reaching more than 75%. 91.28% increase of 21.70%; The results of improving the performance of library management through structured coaching of librarians and teachers have reached more than 80%